2011
DOI: 10.1016/j.jmb.2010.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Induced Conformational Changes Occur in All Cleaved Forms of Caspase-6

Abstract: Caspase-6 is an apoptotic cysteine protease that also governs disease progression in Huntington’s and Alzheimer’s Diseases. Caspase-6 is of great interest as a target for treatment of these neurodegenerative diseases, however the molecular basis of caspase-6 function and regulation remains poorly understood. In the recently reported structure of caspase-6, the 60’s and 130’s helices at the base of the substrate-binding groove extend upward, in a conformation entirely different from that of any other caspase. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 66 publications
(65 reference statements)
5
98
0
Order By: Relevance
“…However, in cathepsin B (35), the prodomain is only weakly associated with the enzyme, through five hydrogen bonds, and it crosses the active site in the opposite orientation to that observed in MCA2. Structural elucidation of a caspase prodomain is yet to be achieved, but it has been reported to be flexible, and hence disordered, in the crystal structures (36). In contrast, the N-terminal domain of MCA2 was both visible and highly ordered in our crystal structures, with its position clearly showing that it would be required to undergo a conformational shift to allow substrates access into the active site.…”
Section: Resultsmentioning
confidence: 73%
“…However, in cathepsin B (35), the prodomain is only weakly associated with the enzyme, through five hydrogen bonds, and it crosses the active site in the opposite orientation to that observed in MCA2. Structural elucidation of a caspase prodomain is yet to be achieved, but it has been reported to be flexible, and hence disordered, in the crystal structures (36). In contrast, the N-terminal domain of MCA2 was both visible and highly ordered in our crystal structures, with its position clearly showing that it would be required to undergo a conformational shift to allow substrates access into the active site.…”
Section: Resultsmentioning
confidence: 73%
“…Generation of Caspase-6 Variants-The wild-type caspase-6 constructs consisted of a synthetic gene encoding the Escherichia coli codon-optimized, full-length, C-terminal His 6 -tagged human CASPASE-6 gene comprising amino acids 1-293 plus His 6 ligated into the NdeI/BamHI sites of the pET11a vector (Stratagene) or from a constitutive two-chain (CT) 3 version of the synthetic CASPASE-6 gene (Celtek Bioscience) (16). Amino acid substitutions were introduced by the QuikChange site-directed mutagenesis method (Stratagene) in the fulllength construct or the CT construct.…”
Section: Methodsmentioning
confidence: 99%
“…3B). Caspase-6 is the only caspase known to exist in a latent, highly helical conformation where the 60s and 130s helices are elongated and the 90s helix is rotated out relative to the canonical fold (16,18). We soaked zinc into crystals of this helical conformation and found that the zinc-bound structure remains in the latent helical form (Fig.…”
Section: Zinc Is the Only Transition Metal To Inhibit Caspase-6-amentioning
confidence: 99%
See 1 more Smart Citation
“…To further determine how palmitoylation of CASP6 might affect its processing and activation (Figure 4a), we utilized computational molecular modelling based on the published crystal structures of CASP6. 24,25,[49][50][51][52][53][54][55] Generation of the model of CASP6 required the construction of coordinates of loop 2 (L2), which forms the substrate-binding groove (active site) and is not resolved in any of the several crystal structures available, presumably owing to high flexibility. The structure of CASP6 has a six-stranded β-sheet flanked by five α-helices and two small β-strands.…”
Section: Resultsmentioning
confidence: 99%